Assessing the Impacts of Non-Ricardian Households in an Estimated New Keynesian DSGE Model - Ricardo Marto (Swiss Journal of Economics and Statistics, 2014)
A New Keynesian DSGE model with non-Ricardian households is estimated for the Portuguese economy and the stability of the model's prediction (posterior distributions, impulse responses, and sources of fluctuations in endogenous variables) tested under different assumptions on non-Ricardian households. Their share is estimated to be relatively high (58 %). Furthermore, estimates of several parameters as well as the magnitude and persistence of shocks are particularly sensitive to the share of non-Ricardian households. Impulse responses to consumption preference and productivity shocks are amplified for lower shares;for greater proportions, the model predicts more noticeable responses to price markup and government spending shocks. Fluctuations in output growth are mainly driven by productivity shocks for a lower share and by price markup shocks in the opposite scenario. A high proportion of these households together with a high degree of price stickiness lead the Taylor-type interest rate rule solution to be locally indeterminate.
Keywords: C11; E12; E37; E52; E62; 330; DSGE; New Keynesian model; non-Ricardian households; Bayesian inference; Portugal